Distinct Polarization Dynamics of Microglia and Infiltrating Macrophages: A Novel Mechanism of Spinal Cord Ischemia/Reperfusion Injury - Li H; Wang P; Tang L; Sun J; Zhang Y; Luo W; Luo C; Hu Z; Yang L (Journal of Inflammation Research, 2021)
Hui Li,1,2 Pengfei Wang,1,2 Lin Tang,1,2 Jingjing Sun,1,2 Yanling Zhang,1,2 Wei Luo,1,2 Cong Luo,1,2 Zhaolan Hu,1,2 Lin Yang1,2 1Department of Anesthesiology, The Second Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 2Hunan Province Center for Clinical Anesthesia and Anesthesiology, Research Institute of Central South University, Changsha, People’s Republic of ChinaCorrespondence: Lin YangDepartment of Anesthesiology, The Second Xiangya Hospital, Central South University, Changsha, People’s Republic of ChinaFax +86 73185295970Email linyang@csu.edu.cnPurpose: Recent studies indicate that microglia and monocyte-derived macrophages (MDMs) have different roles in diseases such as stroke and spinal cord injury, yet their respective polarized phenotypes and roles remain unclear in spinal cord ischemia/reperfusion injury (SCIRI).Methods: We established a mouse model of SCIRI by transient aortic occlusion followed by reperfusion. Basso mouse scale (BMS) scores were used to test the locomotor functions. The histopathological changes in spinal cord were assessed by hematoxylin-eosin staining and NF-200 immunohistochemistry. Real-time PCR, immunofluorescence and flow cytometry were employed to analyze the polarized phenotypes of the microglia and infiltrating MDMs, and the resulting inflammatory responses. Furthermore, the role of infiltrating MDMs were investigated by MDMs depletion using systemic administration of clodronate-liposomes.Results: SCIRI significantly impaired locomotor function of mice, accompanied with progressed necrosis, infiltration of inflammatory cells and neuron loss in the spinal cord. M1-related pro-inflammatory markers (iNOS, CD16, CD86 and TNF-α) increased dramatically in the early phase following SCIRI. In contrast, M2-related anti-inflammatory markers (CD204 and CD206) elevated at later stage. Besides, the invading MDMs were principally pro-inflammatory M1 type, transiently restricted to the first week after SCIRI. In contrast, microglia were the main source of anti-inflammatory M2 type. Furthermore, depletion of MDMs by clodronate-liposomes significantly preserved neurological functions and relieved neuronal damage caused by SCIRI.Conclusion: These findings suggested distinct polarized status of resident microglia and MDMs following SCIRI. Inhibition of the invading MDMs may represent a novel approach for SCIRI treatment.Keywords: spinal cord ischemia/reperfusion injury, microglia, monocyte derived macrophages, polarization, inflammation